Development of Traditional Musician Sasando Viola at the Location of Sasandu Craft Development (Lokabinkra) in Kupang City, East Nusa Tenggara - Kabnani, Jefri Soli (KnE Social Sciences, 2024)
The purpose of this research is to find out the efforts made in developing Sasando musicians. The results of the study show that there are several factors causing the lack of the number of Sasando musicians in Kupang city. This is because the development of modern music is so significant that traditional musical instruments are considered obsolete, old-fashioned, and one that cannot compete with the outside world. One reason is the lack of attention from the local government regarding the development of the traditional sasando musical instrument for the development of regional culture of the people of East Nusa Tenggara, especially the people of Kupang City. Keywords: development of traditional musicians, Sasando music, Sasandu gong, Sasando biola